FEATURES OF MEASURING THE EFFECTS OF WATER TREATMENT WITH A MAGNETIC FIELD - RADOVENCHYK, VIACHESLAV; VOSCHCHENKO, BOHDAN; MENOVSHCHIKOVA, ALENA; RADOVENCHYK, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The catastrophic deterioration of the quality of natural waters prompts intensive research in the field of water treatment and purification technologies. At the same time, special preference is given to technologies that are not associated with the use of additional reagents and secondary pollution of consumed water. One of such promising areas is the use of a magnetic field in water treatment technologies. However, today, even in the most studied field of using a magnetic field to protect power equipment from scale formation, there is no consensus on the dominant processes and factors. Therefore, it is obvious that research in this field is relevant and timely. The conducted cycle of experiments on reliable fixation of the effects of the magnetic field on aqueous solutions with increased rigidity allows us to assert that indirect control methods in the form of specific electrical conductivity or hydrogen index cannot adequately describe changes in the treated solutions. Changes in the specified parameters are so insignificant that they are leveled against the background of their initial values. To reliably record the decrease in hardness of natural waters as a result of treatment with a magnetic field, it is advisable to measure the residual hardness after prolonged treatment at elevated temperatures. We have established that the closest to real operating conditions is the installation of a heating element directly in the thickness of the solution under study. In this case, it is possible to record the balance of hardness ions, which will be divided into three parts - the residual hardness of the liquid phase, the solid phase in the form of sediment and the solid phase in the form of scale. The study of the processes of formation of the specified three parts shows that the optimal temperature for processing during the analysis is not lower than 60 - 70 ° C and the processing time at this temperature is not less than 60 minutes. Under these conditions, the overwhelming number of possible calcium carbonate particles crystallizes and further increase and extension of the specified parameters does not significantly affect the result.
Keywords: softening; magnetic field; hydrogen indicator; electrical conductivity of the solution; magnetic induction